Evidence for temporal disintegration of information processing during sensorimotor integration in GTS - Yifan Hao; Paul Wendiggensen; Annet Bluschke; Tina Rawish; Julia Friedrich; Eszter Tóth-Fáber; Zsanett Tárnok; Veit Roessner; Christian Frings; Anne Weissbach; Tobias Bäumer; Alexander Münchau; et al. (NeuroImage: Clinical, 2025)
In Gilles de la Tourette syndrome (GTS), a neuropsychiatric disorder defined by the presence of tics, bindings of perceptual and motor processes in what cognitive theories refer to as event files is altered. The neural basis of such abnormal coupling though is currently unclear, particularly as regards oscillatory activity in theta, alpha, and beta frequency bands. The inter-relation between oscillatory activities in the theta, but also the alpha and beta band during event file binding and retrieval was investigated in the present study in patients with GTS and healthy controls (HC) using a well-established stimulus–response event file task and concomitant EEG recording. Behaviorally, binding effects did not differ between groups. Also, there were well-known patterns of theta, alpha and beta band activity during retrieval in both groups. In addition, corroborating previous findings in HC, in the period after event file binding and before retrieval, theta, alpha and beta band activity was found in the insula cortex, inferior/middle frontal and superior/middle temporal areas of the right hemisphere in both groups. However, in comparison to HC, GTS patients exhibited relatively less widespread oscillatory correlations between the post-binding and retrieval periods. Notably, a correlation between beta-band oscillations in the supplementary motor area (SMA) and oscillatory activity during the post-binding period was observed only in HC, but not in GTS. This absence in GTS may reflect a disrupted management of event files following retrieval. Overall, the findings suggest a relative decoupling of oscillatory activity associated with binding and retrieval processes in individuals with GTS.